Exploring the association between circRNA expression and pediatric obesity based on a case-control study and related bioinformatics analysis - Guobo Li; Xingyan Xu; Le Yang; Yingying Cai; Yi Sun; Jianhui Guo; Yawen Lin; Yuduan Hu; Mingjun Chen; Huangyuan Li; Siying Wu (BMC, 2023)
Abstract Objective Our present study utilized case-control research to explore the relationship between specific circRNAs and pediatric obesity through a literature review and bioinformatics and to predict their possible biological functions, providing ideas for epigenetic mechanism studies of pediatric obesity. Methods CircRNAs related to pediatric obesity were preliminarily screened by a literature review and qRT-PCR. CircRNA expression in children with obesity (n = 75) and control individuals (n = 75) was confirmed with qRT-PCR in a case-control study. This was followed by bioinformatics analyses, such as GO analysis, KEGG pathway analysis, and ceRNA network construction. Multivariate logistic regression was utilized to analyze the effects of circRNAs on obesity. A receiver operating characteristic (ROC) curve was also drawn to explore the clinical application value of circRNAs in pediatric obesity. Results Has_circ_0046367 and hsa_circ_0000284 were separately validated to be statistically downregulated and upregulated, respectively, in the peripheral blood mononuclear cells of children with obesity and revealed as independent indicators of increased CHD risk [hsa_circ_0046367 (OR = 0.681, 95% CI: 0.480 ~ 0.967) and hsa_circ_0000284 (OR = 1.218, 95% CI: 1.041 ~ 1.424)]. The area under the ROC curve in the combined analysis of hsa_circ_0046367 and hsa_circ_0000284 was 0.706 (95% CI: 0.623 ~ 0.789). Enrichment analyses revealed that these circRNAs were actively involved in neural plasticity mechanisms, cell secretion and signal regulation. Conclusion The present research revealed that low expression of hsa_circ_0046367 and high expression of hsa_circ_0000284 are risk factors for pediatric obesity and that neural plasticity mechanisms are closely related to obesity.